Traffic Signal Design For Janglat Mandi Anantnag as Per Webster’s And Irc Method (International Journal of Innovative Research in Computer Science & Technology, 2022)
The increasing of traffic volume at our  intersection has been arise a problems like road accidents,  conflicts and congestions. These problems can now only  be solved by providing an efficient traffic control at  intersections and that can be achieved by provision of  traffic signal system at intersections for continuous and  efficient movement of vehicles through the intersections.  According to traffic signal, signal timing is most important  which is used to decide green time of the traffic light shall  be provided at an intersection and how long the  pedestrian walk signal should be provided. Traffic volume  studies are to be made to determine the number,  movement and classification of vehicles at the given  location. These data is used identify normal flow of the road;  determine the influence of heavy vehicles or pedestrians  on vehicular traffic volume. The length of the sampling  period depends on the type of count being taken.  According to manual count with 15-minute intervals could  be used to obtain the traffic volume data. The collected data  is converted into PCU units. Passenger Car Unit (PCU) is  the metric used to convert heterogenic traffic in to  homogenous traffic. In India traffic pattern is  heterogeneous, it is necessary to convert heterogeneous  traffic to homogenous traffic while designing any  signalized intersection. PCU Value is dynamic in Nature.  PCU value is depends upon current road traffic condition.  In India PCU value is based on value given in IRC SP 41.  Developed countries devised several methods for  calculating PCUs. Webster’s method is a rational approach  for signal design. The design is simple and is totally  based on formulae’s laid down by Webster. In this  research work the traffic signal for Janglat Mandi chowk  is designed by the various traffic surveys.
Keywords: Traffic Signal; Traffic control; cycle length and warrants; Irc; Webster’s; Pcu; Traffic Fields